Yes or No: How children combine gestures and speech to express honest and deceiving attitude - Marc Swerts; Yan Gu; Tarissa Boerrigter (University of Groningen Press, 2022)
This study looks into children's use of head gestures to express their appreciation for objects, comparing cases in which the gestures match or do not match their true attitude. Forty-four children aged 5 to 8 years old were asked to tell an experimenter whether or not they would like to have shown objects as presents for their birthday. In a first round, children were not given any additional instructions, so that their feedback matched their genuine attitude towards the objects. In a second round, they were asked to give feedback in a way that was the opposite of what they felt. Analyses of their verbal reactions and response delays suggest that the youngest children found it harder to produce incongruent feedback. While the relative use of head gestures decreases with age, children in all age groups produce more head gestures in the congruent condition, and produce more shaking gestures.  Keywords: head gestures, signs of attitude, child development.